Measuring walking accessibility to public transport for the elderly: the case of Naples - Papa, Enrica; Carpentieri, Gerardo; Guida, Carmen (TeMA - Journal of Land Use, Mobility and Environment, 2018)
Demographic ageing represents an essential challenge for local authorities and public transport providers. Decision-makers should not ignore the speci c needs of this weak segment of the population and should implement appropriate policies. This paper develops a GIS-based method to analyse public transport accessibility of elderly people to support policies and planning strategies. To test the proposed method, we propose an application to the city of Naples in Italy. We selected this study case because it represents an example of high population density, complex urban structure and low level of quality of life, especially for the elderly. The application to the city of Naples showed that the urban accessibility changes dramatically for different age segments. Results also reveal patterns of public transport coverage that are signi cantly low particularly in suburban settings. The structure of this paper is organised into four sections: in the rst section, we introduce the main topic of mobility of elderly; in the second section, we describe and discuss the GIS-based method proposed; in the third section, we report on the application to the city of Naples; in the last section, we analyse the results and discuss future research developments.